Bibliometric Analysis for Modeling in Construction Risk Management: A Literature Review - Ghodosi, Mohamad; Zeinalnezhad, Masoomeh; Kazemi , Abolfazl (Management Strategies and Engineering Sciences, 2025)
Effective risk management and strategic planning are critical determinants of success in construction projects. To explore the academic landscape surrounding construction risk management, a total of 284 scholarly sources were systematically reviewed. These included 222 journal articles, 36 conference proceedings, 21 books, one doctoral dissertation, two master's theses, and two patents, all published between 2000 and 2024. The literature was identified through rigorous searches of academic databases, digital libraries, and scientific search engines. The analysis reveals that while conventional approaches—such as Work Breakdown Structure (WBS), regional strategies, and equilibrium-based frameworks—remain in use, increasing scholarly attention has been directed toward mathematical modeling techniques grounded in optimization theory. These models are favored for their enhanced efficiency and efficacy in selecting risk response strategies within construction environments. The advanced model identified in the literature integrates multi-objective optimization, accounting not only for traditional parameters such as time, cost, and quality, but also for project resilience and resource fluctuation control. Notably, the incorporation of plan resilience and resource fluctuation control into an optimization-based risk management framework marks a significant innovation in the field. Furthermore, this model supports the concurrent identification and evaluation of both influential and affected risks, enabling the development of synchronized response strategies that foster synergistic risk mitigation. Application of this model in large-scale and high-rise construction projects demonstrates its potential to improve overall project outcomes by systematically balancing key performance objectives.